Tumor-Targeting Glycol Chitosan Nanoparticles for Cancer Heterogeneity - Ryu, Ju Hee; Yoon, Hong Yeol; Sun, In-Cheol; Kwon, Ick Chan; Kim, Kwangmeyung (WILEY-V C H VERLAG GMBH, 2020)
Nanomedicine is extensively employed for cancer treatment owing to its unique advantages over conventional drugs and imaging agents. This increased attention to nanomedicine, however, has not fully translated into clinical utilization and patient benefits due to issues associated with reticuloendothelial system clearance, tumor heterogeneity, and complexity of the tumor microenvironment. To address these challenges, efforts are being made to modify the design of nanomedicines, including optimization of their physiochemical properties, active targeting, and response to stimuli, but these studies are often performed independently. Combining favorable nanomedicine designs from individual studies may improve therapeutic outcomes, but, this is difficult to achieve as the effects of different designs are interconnected and often conflicting. Glycol chitosan nanoparticles (CNPs) are shown to accumulate in tumors, suggesting that this type of nanoparticle may constitute a good basis for the additional modification of nanoparticles. Here, multifunctional glycol CNPs designed to overcome multiple obstacles to their use are described and key factors influencing in vivo targeted delivery, targeting strategies, and interesting stimulus-responsive designs for improving cancer nanomedicine are discussed.
Keywords: SELF-ASSEMBLED NANOPARTICLES; SUPERPARAMAGNETIC IRON-OXIDE; FREE CLICK CHEMISTRY; GUIDED PHOTOTHERMAL THERAPY; IN-VIVO; DRUG-DELIVERY; MATRIX METALLOPROTEINASES; CELLULAR UPTAKE; SURFACE-CHARGE; BREAST-CANCER